Critical security challenges in cloud computing environment: An appraisal - Mir, Mohammad Shuaib; Suhaimi, Mohd Adam; Khan, Burhan Ul Islam; Mattoo, M. Mueen Ul Islam; Funke Olanrewaju, Rashidah (Journal of Theoretical and Applied Information Technology, 2017)
This paper mainly contributes a comprehensive survey on the climacteric security challenges imposed by cloud computing. The paper highlights the challenges/loopholes existing in cloud environment despite all the efforts adopted by organizations, and offers the recommendations for cloud providers as well as users. In this paper, more than 20 research papers pertaining to cloud security, in the span of past 5 years, have been studied and analyzed and twelve most important security threats to organizations have been identified that need attention by research community for encouraging their cloud adoption. This review concludes that some measures have to be adopted for accomplishing complete security in all aspects in the cloud environment. Unlike previous approaches, this effort is directed towards providing a thorough and inclusive review of the security vulnerabilities in cloud. Furthermore, this paper tries to suggest means how cloud federations can enhance security while mitigating risk and building customer trust at the same time.